SS Pajakoemboeh: Perkembangan Transportasi Kereta Api di Afdeeling Limapuluh Kota berdasarkan Tinjauan Arkeologi - Dwi Kurnia Sandy; Salma Fitri Kusumastuti (Berkala Arkeologi, 2026)
The railway transportation system in West Coast of Sumatra (Sumatra’s Westkust Residentie) developed rapidly in accordance with coal distribution from the Ombilin Mines in Sawahlunto. The Dutch East Indies government established Staatsspoorwegen ter Sumatra's Westkust (SSS) as the main operator for railway construction, initially aimed at connecting Ombilin Mine to Teluk Bayur Port. Over time, the railway network was also utilized for transporting agricultural products from the interior regions, including Afdeeling Limapuluh Kota. Research findings indicate that Payakumbuh Station in Afdeeling Limapuluh Kota played a crucial role as a transportation hub connecting various areas. The construction of railway lines in this region had a significant economic and social impact by accelerating natural resources distribution and enhancing mass transportation. However, many historical railways remain in this area are now in a deteriorated condition. Therefore, preservation efforts are necessary to safeguard the cultural heritage of railway transportation in Sumatra’s Westkust Residentie.